The Effect of Untethering on Urologic Symptoms and Urodynamic Parameters in Children With Primary Tethered Cord Syndrome - DAĞÇINAR, ADNAN; BAYRİ, YAŞAR (ELSEVIER SCIENCE INC, 2015)
OBJECTIVE To evaluate urinary system symptoms (USSs) and urodynamic parameters (UPs) before and after untethering in children with primary tethered cord syndrome (pTCS). METHODS USSs and UPs of patients undergoing untethering for pTCS during the period January 2008-July 2012 were evaluated preoperatively and at the postoperative third and 12th months. For analysis, patients were separated into 4 groups according to the presence of USSs: group 1, USSs preoperative positive and postoperative negative; group 2, USSs preoperative positive and postoperative positive; group 3, USSs preoperative negative and postoperative positive; group 4, USSs preoperative negative and postoperative negative. Preoperative and postoperative USSs and UPs were compared. RESULTS Forty patients (average age, 7.2 years, follow-up of 2.8 years) were included. There were 13 patients in group 1, 11 in group 2, 3 in group 3, and 13 in group 4. All patients showed improvement when preoperative and postoperative USSs and UPs were compared. There was no correlation between USSs and UPs, both preoperatively and postoperatively. USSs and UPs at the postoperative third and 12th months were similar. Patients with no USS showed the most significant improvement in UP after untethering. CONCLUSION Our study has demonstrated that untethering in patients with pTCS improves urologic symptoms and UPs. However, there is no correlation between improvement in symptoms and urodynamic findings. Urodynamic changes are similar at the postoperative third and 12th months. As the most significant improvement was seen in patients without USSs, it is important that these patients undergo urodynamic studies preoperatively and postoperatively. (C) 2015 Elsevier Inc.
Keywords: SPINAL DYSRAPHISM; BLADDER DYSFUNCTION; RELEASE